Resting-state functional connectivity of amygdala subregions across different symptom subtypes of obsessive–compulsive disorder patients - Harah Kwon; Minji Ha; Sunah Choi; Sunghyun Park; Moonyoung Jang; Minah Kim; Jun Soo Kwon (NeuroImage: Clinical, 2024)
Aim: Obsessive–compulsive disorder (OCD) is a heterogeneous condition characterized by distinct symptom subtypes, each with varying pathophysiologies and treatment responses. Recent research has highlighted the role of the amygdala, a brain region that is central to emotion processing, in these variations. However, the role of amygdala subregions with distinct functions has not yet been fully elucidated. In this study, we aimed to clarify the biological mechanisms underlying OCD subtype heterogeneity by investigating the functional connectivity (FC) of amygdala subregions across distinct OCD symptom subtypes. Methods: Resting-state functional magnetic resonance images were obtained from 107 medication-free OCD patients and 110 healthy controls (HCs). Using centromedial, basolateral, and superficial subregions of the bilateral amygdala as seed regions, whole-brain FC was compared between OCD patients and HCs and among patients with different OCD symptom subtypes, which included contamination fear and washing, obsessive (i.e., harm due to injury, aggression, sexual, and religious), and compulsive (i.e., symmetry, ordering, counting, and checking) subtypes. Results: Compared to HCs, compulsive-type OCD patients exhibited hypoconnectivity between the left centromedial amygdala (CMA) and bilateral superior frontal gyri. Compared with patients with contamination fear and washing OCD subtypes, patients with compulsive-type OCD showed hypoconnectivity between the left CMA and left frontal cortex. Conclusions: CMA–frontal cortex hypoconnectivity may contribute to the compulsive presentation of OCD through impaired control of behavioral responses to negative emotions. Our findings underscored the potential significance of the distinct neural underpinnings of different OCD manifestations, which could pave the way for more targeted treatment strategies in the future.